Life in an unsuspected antibiotics world: River biofilms. (1st March 2023) - Matviichuk, Olha; Mondamert, Leslie; Geffroy, Claude; Dagot, Christophe; Labanowski, Jérôme
Highlights: The dispersed pollution is sufficient to induce selection pressure in river biofilms. Rivers subjected to medium intensity of anthropic pressure are also at risk of resistance development. Antibiotic concentration in biofilms exceeds the MSC-MIC and PNEC several months a year. Abstract: Waterborne bacteria that naturally live in biofilms are continuously exposed to pharmaceutical residues, regularly released into the freshwater environment. At the source level, the discharge of antibiotics into rivers has already been repeatedly linked to the development of antimicrobial resistance. But what about biofilms away from the discharge point? Two rivers, with sites subject to dispersed contamination of medium intensity, were studied as typical representatives of high- and middle-income countries. The biofilms developed on rocks indigenous to rivers are perfectly representative of environmental exposure. Our results show that away from the hotspots, the amount of antibiotics in the biofilms studied favours the maintenance and enrichment of existing resistant strains as well as the selection of new resistant mutants, and these favourable conditions remain over a period of time. Thus, in this type of river, the environmental risk of selection pressure is not only present downstream of urbanized areas but is also possible upstream and far downstream of wastewater treatment plant discharges. Despite this, correlation analysis found no strong positive correlation between antibiotic concentrations and the abundance of measured integrons and their corresponding resistance genes. Nevertheless, this work highlights the need to consider the risks of antibiotics beyond hotspots as well. Graphical abstract: Image, graphical abstract